Environmental assessment of the waters of Mar Ibn Najm - كفاح الاسدي; حسن حسن (آداب الكوفة, 2012)
Through the discussion of this research, it is clear that the temperature of the water of Mar Ibn Najm is suitable for drinking according to the specifications of the World Health Organization, while this water was characterized by a low degree of transparency due to the density of organic matter suspended in this water and the density of aquatic plants, which reduces its suitability for drinking. In terms of turbidity, this water is not suitable for drinking during the summer and suitable for drinking during the winter according to the specifications of the organization (W.H.O). , and the values ​​of nitrates and the values ​​of suspended matter) while it is not suitable for drinking in terms of the values ​​of (electrical conductivity, magnesium, total hardness, sulfates and total dissolved substances)